Persistent thrombocytopenia in Dengue Fever is rare but not uncommon - can be treated with steroid successfully - Islam, Md Daharul; Akter, Khaleda; Chowdhury, Ranajit Sen; Sarkar, Mohammad Abdus Sattar; Rahman, Aminur (Bangladesh Journal of Medicine, 2021)
Fever, skin rash, thrombocytopenia and bleeding are common manifestation of dengue fever (DF). Thrombocytopenia usually gets better and platelet count normalizes by day 10 of fever. Chronic thrombocytopenia is not a feature of dengue fever. Proposed mechanisms behind thrombocytopenia are many. Direct platelet destruction by dengue virus, immune-mediated platelet destruction and evenmegakaryocytic immune injury are proposed as underlying mechanisms. We are reporting a case of a 43 year old female who presented in dengue season in 2019 with fever and bleeding and wasdiagnosed as a case of dengue haemorrhagic fever. She had persistent thrombocytopenia which neededto be treated on the lines of immune thrombocytopenia and responded to steroids. Other causes of thrombocytopenia were ruled out. Bangladesh J Medicine January 2021; 32(1) : 62-64